”Quaestio ethica et politica, utrum honestum natura constet, an vero tantum opinione” by Francisco Tidicaeus : introduction, translation from Latin and commentary - Dreikopel, Tomasz (Folia Toruniensia, 2017)
The study consists of the introduction, translation and commentary to the text written at the beginning of the 1580s by Franciscus Tidicaeus (1554–1617) a doctor of Philosophy and Medicine, a medical doctor and professor in the Academic Gymnasium School in Toruń. The text was published in 1609.